ANALISIS PERAN SOSIALISASI DALAM MENUMBUHKAN KETERTARIKAN GENERASI MILENIAL UNTUK BERINVESTASI PRODUK SYARIAH - Emilia Septiani (Jurnal Ilmiah Akuntansi Indonesia, 2022)
The purpose of this research is to analyze the role of socialization in growing interest in sharia product investment in the millennial generation. The data collection method used is a sample survey with a sampling technique using accidental sampling. The number of respondents in this study were 100 people. The data collection tool used is a questionnaire. The analytical tool in this research is descriptive statistics. The results of this study indicate that 93% of the millennial generation in West Nusa Tenggara know the difference between conventional and sharia financial products; 25% get information on sharia financial products from social media; 100% of the millennial generation are interested in investing in Islamic financial products; and the average of investment interest is high.